Plants for oral biofilms eradication: literature review - Amatul Firdaustia PRATIWI; Hening Tjaturina PRAMESTI; Faisal KUSWANDANI (Dentistry Faculty, 2021)
ABSTRACT Oral Biofilm is a collection of microbial cell colonies related to periodontal diseases and caries. Biofilmbacteria were more resistant to antimicrobial agents than in the planktonic phase. The rapid progression of bacterialresistance to antimicrobial agents such as chlorhexidine has encouraged researchers to find alternative antimicrobialagents from natural plant products with low side effects. The purpose of this review was to summarize plants thatcontain bioactive compounds for biofilm eradication in terms of preventing caries and periodontal diseases. Themethod was used Systematic Review without Metha Analysis. Articles to be reviewed were searched from Pubmed,Cochrane, Science Direct, and Google Scholar databases using the PRISMA method and hand searching. The lastselected articles were analyzed using narrative analysis. There are 1,610 articles specified in the first stage and only18 articles left in the final extraction stage. Plants that contain bioactive compounds for oral biofilm eradicationinclude Piper betle (betel), Psidium sp., Mangifera sp., Mentha sp., Caesalpinia sappan (secang), Baccharis dracunculifolia,Laurus nobilis L. (dafnah), Croton nepetaefolius, Salvadora persica (miswak), Dryopteris crassirhizoma, Diospyros kakiThunb. (persimmon), Ginkgo biloba, Azadirachta indica (neem), Camellia sinensis, Lippia alba, Cymbopogon citratus(lemongrass), Citrus aurantifolius, Tamarindus indica (sour), Syzygium cumini (jamblang), Emblica officinalis (malacca),Acacia Arabica (prickly acacia), Terminalia chebula (myrobalan), Terminalia bellerica (bahera), Carica papaya, Ocimumbasilicum L. (basil), and Myrmercodia pendans. These plant bioactive compounds are belong to the group of alkaloids,terpenoids, and polyphenols which were tested in the form of single compounds or mixtures, especially againstStreptococcus mutans. In conclusion, 26 plant species have reported containing bioactive compounds tested in theform of single or mixed extracts to eradicate oral bacterial biofilm. KEYWORDS: Plants, eradication, natural products, oral biofilm